Pemetaan Partisipatif melalui Transek di Desa Muktisari, Kecamatan Cingambul, Kabupaten Majalengka - Amelia Paramitha Mahanani; Sarah Putri Sylvayanti; Dina Nurdinawati; Yayat Heryatno; Risda Rizkillah; Melani Abdul Kadir (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Transect is one of the Participatory Rural Appraisal (PRA) techniques used to conduct direct observations of the environment and community resources. This activity is carried out by walking through the village area and following a certain path that has been mutually agreed upon. The purpose and benefits of transects are to clearly see the natural conditions and complexity of the farming system, and to maintain limited natural resources run by the community. A description of the natural resources of the Muktisari Village community along with its problems can be obtained from the village transect activities, as well as changes in the village's potential. The village of Muktisari is divided into three parts. The three blocks comprise Ciloa Girang, Karangsari and Ciloa Hilir. Every block in the Village of Muktisari has its own characteristics. There is still a lot of land which has not been optimally used, there are still several plants whose maintenance and manufacturing processes have not been intensively carried out. In the village of Muktisari, soil fertility is beginning to decline and the expertise and attitudes of farmers who still maintain the tradition, making it difficult for communities to introduce new technologies to boost the agricultural activities. Keywords: Observation, The village’s potential, transects